Genotoxic assessment of Rubus imperialis (Rosaceae) extract in vivo and its potential chemoprevention against cyclophosphamide-induced DNA damage - Costa Rodrigues Alves, Ana Beatriz [UNESP]; Santos, Rafaella Souza dos [UNESP]; Calil, Susana de Santana [UNESP]; Niero, Rivaldo; Lopes, Jhonny da Silva; Perazzo, Fabio E.; Pires Rosa, Paulo Cesar; Andrade, Sergio Faloni; Cechinel-Filho, Valdir; Maistro, Edson Luis [UNESP] (Elsevier B.V., 2014)
Ethnopharmacological relevance: Rubus imperialis Cham. Schl. (Rosaceae) is frequently used in traditional medicine as hypoglycemic, antinociceptive and antiviral remedy.Materials and methods: Swiss albino mice were distributed in eight groups for acute treatment with Rubus imperialis extract (24 h). The extract doses selected were 50, 250 and 500 mg/kg b.w. administered by gavage alone or plus to CPA (50 mg/kg b.w.) administered by intraperitoneal injection. Control groups were treated in a similar way. Analyses were performed using the comet assay, on leukocytes (collected 4 and 24 h after treatment) and liver (collected 24 h after treatment), and using the micronucleus test (MN) in bone marrow cells. Cytotoxicity was assessed by scoring 200 consecutive polychromatic (PCE) and normochromatic (NCE) erythrocytes (PCE/NCE ratio).Results and conclusion: The main compounds identified in the Rubus imperialis extract were saponins and steroidal compounds, with niga-ichigoside and tormentic acid being the major compounds. Tested doses of Rubus imperialis extract showed no genotoxic effects on leukocytes from peripheral blood or liver cells by the comet assay. However, the MN test showed an increase in the frequency of micronucleated cells at the two higher doses tested, indicating that this extract has clastogenic/aneugenic effects on bone marrow cells at higher doses. On the other hand, for all cells evaluated, the three tested doses of the Rubus imperialis extract promoted inhibition of DNA damage induced by CPA. Despite the chemoprevention observed, the clastogenicity/aneugenicity observed suggested caution about either continuous or high-dose usage of Rubus imperiale aerial parts extract by humans. (C) 2014 Elsevier Ireland Ltd. All rights reserved.
Keywords: Rubus imperialis; Rosaceae; Comet assay; Micronucleus test; Antigenotoxic effects